Neoliberalism : a critical reader - Saad-Filho, Alfredo, 1964-; Johnston, Deborah, 1967- (Pluto Press, 2005)
"Bravo! Some of the most incisive students of neoliberalism gather together to present a stunning indictment of the destructiveness of the already discredited right-wing economic régime." Professor Michael Perelman, California State University, Chico "Across its thirty chapters, covering theoretical, empirical, policy and political aspects for different regions of the world, this collection of essays on neo-liberalism establishes that it is not merely a temporary phase of contemporary capitalism. Rather, it is the reflection of deep-rooted structures and processes, forging a rhythm in capitalist development that inevitably releases appalling consequences albeit in historically specific circumstances. In short, neo-liberalism, like imperialism, underdevelopment, fascism, world wars and so on, is not some aberration but an immanent aspect of capitalism." Professor Ben Fine, School of Oriental and African Studies, University of London "This scholarly yet deeply engaged book will do much to to put the record straight on what neoliberalism is and what its actual effects have been on those who have gained from it and the much larger numbers who have been afflicted by it. The geographical scope and analytical sophistication of the contributions make it one of the few really reliable guides to this complex and life-threatening ideology." Professor Leslie Sklair, London School of Economics Neoliberalism is the dominant ideology shaping our world today. It dictates the policies of governments, and shapes the actions of key institutions such as the WTO, IMF, World Bank and European Central Bank. Its political and economic implications can hardly be overstated. Yet there are obvious problems with the neoliberal project. This book is a perfect introduction to neoliberalism that is ideal for anyone seeking a critical perspective. It explains the nature, history, strengths, weaknesses and implications of neoliberalism from the point of view of radical political economics. Short, self-contained chapters are written by leading experts in each field. The books is organised in three parts: the first section outlining neoliberal theory, the second exploring how neoliberalism has affected various policy areas, and a third looking at how neoliberal policies have played out in particular regions of the world. Using a broad range of left economic perspectives, from post-Keynesian to Marxist, this is a great resource for students of politics and economics, and anyone looking for a grounded critical approach to this broad subject.